2023
DOI: 10.3390/pharmaceutics15051348
|View full text |Cite
|
Sign up to set email alerts
|

Comprehensive Insights into Medicinal Research on Imidazole-Based Supramolecular Complexes

Abstract: The electron-rich five-membered aromatic aza-heterocyclic imidazole, which contains two nitrogen atoms, is an important functional fragment widely present in a large number of biomolecules and medicinal drugs; its unique structure is beneficial to easily bind with various inorganic or organic ions and molecules through noncovalent interactions to form a variety of supramolecular complexes with broad medicinal potential, which is being paid an increasing amount of attention regarding more and more contributions… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
9
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 27 publications
(13 citation statements)
references
References 496 publications
(568 reference statements)
0
9
0
Order By: Relevance
“…Products with diverse biological activities are especially common among imidazole derivatives. 1 Furthermore, the imidazole core is present in functional materials such as chiral catalysts, 2 polymers, 3 ligands, 4 and electroluminescent devices. 5 It means that synthetic methodologies for the preparation and functionalization of this versatile heterocycle are of great interest and is an area of intensive research.…”
Section: Introductionmentioning
confidence: 99%
“…Products with diverse biological activities are especially common among imidazole derivatives. 1 Furthermore, the imidazole core is present in functional materials such as chiral catalysts, 2 polymers, 3 ligands, 4 and electroluminescent devices. 5 It means that synthetic methodologies for the preparation and functionalization of this versatile heterocycle are of great interest and is an area of intensive research.…”
Section: Introductionmentioning
confidence: 99%
“…Several recent studies have reported the use of new catalytic systems to produce a new range of molecules [ 29 , 30 , 31 ]. In recent years, imidazole scaffolds have been a vital class of important heterocycles due to their abundance in natural products and their extensive use in medicinal chemistry [ 32 , 33 ]. Several derivatives of imidazole are found within the structure of bioactive substances, encompassing anti-inflammatory [ 34 ], antidiabetic [ 35 ], antituberculosis [ 36 ], antifungal [ 37 ], antimalarial [ 38 ], and anticancer [ 39 ].…”
Section: Introductionmentioning
confidence: 99%
“…Imidazole and its derivatives are the most prevalent versatile units of heterocyclic chemistry, and they possess outstanding pharmaceutical activities to control cancer. Clinical trials have evaluated the efficacy of various imidazole-containing drugs, including dacarbazine, temozolomide, etanidazole, azathioprine, zoledronic acid, pimonidazole, misonidazole, mercaptopurine, nilotinib, fadrozole, and tipifarnib, in the treatment of various types of cancer, with the current availability for clinical use. , Recently, our research efforts have focused on conducting comprehensive studies aimed at developing highly potent anticancer agents. There are numerous scientific studies available which employ innovative and novel synthetic methods to synthesize 2,4,5 tri- and 1,2,4,5 tetra-substituted imidazole heterocyclic compounds. New hybrid molecules with potent biological activities are produced by the molecular hybridization approach, involving two or more biologically active pharmacophores. The combination of these two significant moieties could lead to possible imidazole–pyridine hybrid molecules with enhanced biological activities. The introduction of the hetero unit on position 2 of the imidazole scaffold exhibits potential anticancer activity . In addition, the phenyl rings present at positions 4 and 5 are increasingly crucial for the cytotoxicity of the imidazole moiety when compared to aliphatic substitution on these positions .…”
Section: Introductionmentioning
confidence: 99%